2019
DOI: 10.1002/jcu.22705
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal sonographic diagnosis of biliary tract malformations

Abstract: Congenital anomalies of the biliary tract include a variety of pathologic conditions, such as biliary atresia, choledochal cysts, gallbladder agenesis, congenital cholelithiasis, and gallbladder duplication. Although most of these malformations are rare and benign conditions, they may occasionally represent a major threat to extrauterine life. Visualization of a normal‐sized gallbladder should be a mandatory component of the second‐trimester anomaly ultrasound scan. Advances in prenatal sonography enable the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…In addition, on prenatal studies, the cysts in the CC group were all larger than 1 cm and showed a tendency for gradual growth after birth, while the cyst in the cBA group for which information was available was smaller than 1 cm and stable in size. Other studies also mentioned that the cyst size in infants with cBA was stable during follow-up in the prenatal period [20,27,28] and smaller than that reported in a postnatal study [4], even though the size itself varied considerably across infants (0.5-4.0 cm). Obliteration between the intrahepatic and extrahepatic bile ducts in BA, rather Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, on prenatal studies, the cysts in the CC group were all larger than 1 cm and showed a tendency for gradual growth after birth, while the cyst in the cBA group for which information was available was smaller than 1 cm and stable in size. Other studies also mentioned that the cyst size in infants with cBA was stable during follow-up in the prenatal period [20,27,28] and smaller than that reported in a postnatal study [4], even though the size itself varied considerably across infants (0.5-4.0 cm). Obliteration between the intrahepatic and extrahepatic bile ducts in BA, rather Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The morphology of GB plays an important role in both prenatal and postnatal imaging. A small or nonvisible GB in the second trimester increases the suspicion of BA on prenatal US [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed that cyst communication with the GB may facilitate the diagnosis of CC [ 18 ]. In the 35 CC cases analyzed herein, a GB-cyst connection was observed in 32 cases (91.4%), except in three cases where the cysts were relatively long (≥4.3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a cyst in the right upper abdomen and small gallbladder suggests the diagnosis of congenital anomalies of the biliary tract. 12 However, the association of small gallbladder and CC has not been described in intrauterine life. The differential diagnosis of CC and biliary atresia may be difficult during pregnancy.…”
Section: Discussionmentioning
confidence: 99%